Error exponent for TAS/MRC fading channel - Changshui LI (Dianxin kexue)
Using Meijer-G function,exact expression for the random coding error exponent,ergodic capacity,cutoff rate,expurgated exponent of TAS/MRC Nakagami-m fading channel were derived.Numerical results show that the random coding error exponent is related to channel fading coefficient,coding rate,the number of transmitting and receiving antennas,and signal symbol period.With the coding rate,the number of the receiving and transmitting antennas and the average signal to noise ratio increasing,the RCEE of the system will become larger and the BER performance of the system will be better.For a given decoding error probability of a wireless communication system,necessary coding length,number of antennas,channel coherence time,and spatial fading correlation could be estimated by computing the random coding error exponent.